2021
DOI: 10.1111/bph.15643
|View full text |Cite
|
Sign up to set email alerts
|

Transient Receptor Potential channels, TRPV1 and TRPA1 in melanocytes synergize UV‐dependent and UV‐independent melanogenesis

Abstract: Background and Purpose: Melanogenesis is essential for pigmentation and deregulated melanogenesis causes pigmentary diseases. Psoralen and ultraviolet A (PUVA) therapy strongly stimulates pigmentation, but the underlying molecular mechanisms are elusive. Experimental Approach: Melanin content of cultured human melanocytes was spectrophotometrically measured. Patch-clamp recordings were made in human melanocytes or HEK 293 cells transiently expressing wild type or mutant human TRPV1 and TRPA1 channels. Endogeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
(167 reference statements)
0
3
0
Order By: Relevance
“…Hence, agreeing with our results, inhibition of TRPA1 seem to have a miner effect on the protein expression of gp100, but a major effect on melanin content. Additionally, in 2021, Jia et al 37 found that PUVA‐induced melanogenesis required TRPV1‐ and TRPA1‐mediated Ca 2+ influx in melanocytes. Consistent with this, our results also revealed a corresponding increase or decrease in UVB‐induced skin pigmentation with activation or inhibition of TRPA1 in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, agreeing with our results, inhibition of TRPA1 seem to have a miner effect on the protein expression of gp100, but a major effect on melanin content. Additionally, in 2021, Jia et al 37 found that PUVA‐induced melanogenesis required TRPV1‐ and TRPA1‐mediated Ca 2+ influx in melanocytes. Consistent with this, our results also revealed a corresponding increase or decrease in UVB‐induced skin pigmentation with activation or inhibition of TRPA1 in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, agreeing with our results, inhibition of TRPA1 seem to have a miner effect on the protein expression of gp100, but a major effect on melanin content. Additionally, in 2021, Jia et al 37 ] im and the biological responses in melanosomes. 39 In 2016, Ambrosio et al 30 proposed that knockout of the gene encoded twopore channel 2 (TPC2) protein, a cation release channel expressed in the melanosome-limiting membrane in human melanocytes, produced a decrease of the peri-melanosomes calcium concentration and an increase in melanosome luminal pH, eliciting a significant increase in melanin content and larger size of melanosomes.…”
Section: Topical Treatment With Trpa1 Specific Antagonist Hc-030031 M...mentioning
confidence: 99%
“…A densitometric analysis of the pigmented dish was determined using the ImageJ software, as described previously for tadpoles [35]. Biochemical determination of melanin synthesis was performed as described previously [38]. Briefly, melanophores were harvested, and the number of cells quantified in a Neubauer counting chamber.…”
Section: Melanin Synthesis Assaymentioning
confidence: 99%